Alternations of White Matter Structural Networks in First Episode Untreated Major Depressive Disorder with Short Duration - Lu, Yi; Shen, Zonglin; Cheng, Yuqi; Yang, Hui; He, Bo; Xie, Yue; Wen, Liang; Zhang, Zhenguang; Sun, Xuejin; Zhao, Wei; Xu, Xiufeng; Han, Dan (Frontiers in Psychiatry, 2017)
It is crucial to explore the pathogenesis of major depressive disorder (MDD) at the early stage for the better diagnostic and treatment strategies. It was suggested that MDD might be involving in functional or structural alternations at the brain network-level. However, at the onset of MDD, whether the whole brain white matter (WM) alterations at network-level are already evident still remains unclear. In the present study, diffusion MRI scanning was adopt to depict the unique WM structural network topology across the entire brain at the early stage of MDD. Twenty-one first episode, short duration (<1 year) and drug-naïve depression patients, and 25 healthy control subjects (HCs) were recruited. To construct the WM structural network, atlas-based brain regions were used for nodes, and the value of multiplying fiber number (FN) by the mean FA along the fiber bundles connected a pair of brain regions were used for edges. The structural network was analyzed by graph theoretic and Network-Based Statistic (NBS) methods. Pearson partial correlation analysis was also performed to evaluate their correlation with the clinical variables. Compared with healthy controls, the MDD patients had a significant decrease in the small-worldness (σ). Meanwhile, the MDD patients presented a significantly decreased subnetwork, which mainly involved in the frontal-subcortical and limbic regions. Our results suggested that the abnormal structural network of the OFC and thalamus, involving the imbalance with the limbic system, might be a key pathology in early stage drug-naive depression. And the structural network analysis might be potential in early detection and diagnosis of MDD.